Project-Based Learning in English for Specific Purposes Instruction in Higher Education: Opportunities and Challenges - Zečević, Snežana M.; Dilparić, Branislava M.; Andrejević, Ana M. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
Project-based learning (PBL) is increasingly recognized as a pedagogically effective approach in English for Specific Purposes (ESP) instruction at the tertiary level of education. As a student-centered model, it offers numerous educational benefits, including enhanced learner motivation, the development of practical skills, and improved collaboration. However, it also entails a range of challenges and limitations, as evidenced in a growing body of theoretical and empirical literature (Becket & Miller, 2006; Fragoulis & Tsiplakides, 2009; Bell, 2010; Đorđević & Blagojević, 2017; Boss & Larmer, 2018; Kniazian et al., 2021; Tuyen & Tien, 2021; Anđelković et al., 2022). This paper employs a qualitative content analysis of selected studies to explore the core dimensions of PBL implementation in ESP instruction. The analysis focuses on: (1) the necessity of integrating PBL activities into ESP curricula in the context of contemporary global society; (2) the key characteristics of the PBL approach; (3) theoretical foundations and guiding principles for its implementation in ESP courses; (4) the opportunities and challenges of PBL in ESP contexts based on students’ perspectives; and (5) pedagogical implications, including limitations and recommendations for further research. The dual aim of this review is to emphasize the pedagogical potential of PBL as a modern, student-centered approach to ESP teaching and to encourage further inquiry into course design and curriculum development aimed at fostering student competences required for meaningful participation in the global knowledge-based society (Popovska & Piršl, 2013, p. 43).